Pengaruh Budaya Organisasi dan Komunikasi Terhadap Kinerja Pegawai Negeri Sipil pada DP2KBP2PA Kota Prabumulih - Aurantia Marina; Muhammad Zulkarnain (PT PUSTAKA CENDEKIA PUBLISHER, 2024)
Various factors, including organizational Culture and communication can influence employee performance. This research aims to determine the influence of organizational Culture and communication on employee performance at the Population Control and Family Planning Service, Women’s Empowerment and Child Protection, Prabumulih City. The research method uses quantitative methods with primary data. Primary data comes from a research questionnaire with a total of 57 respondents. The data analysis technique used is multiple linear regression. The research results based on multiple linear regression showed that organizational Culture and communication positively affected employees' performance at the Population Control and Family Planning Service, Women’s Empowerment and Child Protection, Prabumulih City. The t and F tests show that organizational Culture and communication partially and simultaneously significantly affect employees’ performance at the Population Control and Family Planning Service, Women's Empowerment and Child Protection, Prabumulih City.